High-toughness weather-resistant barrier film as well as in-situ crosslinking preparation method and application thereof

Through the in-situ cross-linking reaction between seaweed polysaccharides and vermiculite, the spacing between vermiculite layers is expanded and nanosheet peeling is achieved, which solves the strength and efficiency problems in the preparation of vermiculite nanosheet films, and a composite film with excellent mechanical and flame retardant properties is prepared, which is suitable for a variety of applications.

CN119570090APending Publication Date: 2025-03-07TARIM UNIV +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411807462.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art has problems of low strength, uncontrollable thickness and low efficiency when preparing vermiculite nanosheet films. The chemical vapor deposition method is costly and the preparation conditions are harsh, making it not suitable for large-scale preparation.

Method used

The in-situ cross-linking preparation method of the interaction between seaweed polysaccharides and vermiculite is adopted. Through the intercalation of seaweed polysaccharides and ionic cross-linking with the vermiculite layer, the spacing between vermiculite layers is expanded, the peeling of vermiculite nanosheets is achieved, and plasticizer is added to improve the flexibility of the film.

Benefits of technology

A composite film with good flame retardant properties, high mechanical strength, environmentally friendly and excellent fresh-keeping performance is prepared, which is suitable for flame retardant, gas barrier and food fresh-keeping applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570090A_ABST
    Figure CN119570090A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of functional film material preparation, and particularly relates to a high-toughness weather-resistant barrier film and an in-situ cross-linking preparation method and application thereof.The high-toughness weather-resistant barrier film is prepared by dispersing two-dimensional layered mineral nanosheets in water and stirring the two-dimensional layered mineral nanosheets to obtain nanosheet suspension liquid; slowly adding biomacromolecular polysaccharide, stirring until the biomacromolecular polysaccharide is completely dissolved, and adding a plasticizer to obtain a membrane casting solution; pouring the film casting solution into a mold, and drying to obtain a film precursor; the film precursor is soaked and cross-linked in a metal ion salt solution coagulating bath, washing and drying are performed after cross-linking are completed, and the high-toughness weather-resistant barrier film is obtained, the composite film is good in mechanical strength, has flame retardance and gas barrier performance and can be applied to flame retardance and storage and fresh keeping of food, and the storage time of the food is prolonged; the preparation method is simple, low in cost, suitable for large-scale popularization, wide in market prospect and friendly to application environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention belongs to the field of functional membrane materials and relates to a high-strength and tough weather-resistant barrier film and an in-situ cross-linking preparation method and application thereof. The two-dimensional vermiculite nanosheet / seaweed polysaccharide composite film prepared with seaweed polysaccharide and vermiculite as raw materials has the advantages of good flame retardancy, high mechanical strength, good freshness preservation performance, and UV resistance, and can be used for flame retardancy and gas barrier. Background technology:

[0002] In daily life, plastic packaging materials are widely used by people. However, with the aggravation of "white pollution", there is an urgent need for a bio-friendly, degradable and low-cost food packaging material. Polysaccharide-based food packaging materials are gradually attracting more and more attention and research due to their unique environmental friendliness, non-toxicity and biodegradability. Such materials include sodium alginate, chitosan, carboxymethyl cellulose, carrageenan, etc. Pure polysaccharide-based packaging materials are often accompanied by moisture sensitivity and low mechanical properties. Mixing inorganic nanomaterials with biopolysaccharide macromolecules will obtain a nanocomposite material that has the advantages of both organic and inorganic materials, and will achieve the effect of solving the above problems.

[0003] Nanocomposites refer to composites that have at least one nanomaterial with a dispersed phase size less than 100nm. They have the characteristics of nanoscale effect, large specific surface area and strong interface interaction. Therefore, the addition of nanomaterials is one of the important methods to obtain high-performance composite materials. In recent years, more and more people have begun to study the blending of nanomaterials with biomacromolecule polysaccharides, so as to perfectly combine the dimensional stability and thermal stability of nanomaterials with the biocompatibility and easy processing of biomacromolecule polysaccharides, so as to obtain excellent performance molecules or nanocomposites, and achieve the effect of "1+1>2".

[0004] Composite materials prepared by common methods are mostly physical mixing, with poor interfacial bonding, resulting in shortcomings in electrical, mechanical, flame retardant and barrier properties. Yu Mingming et al. (Chemical Engineering Journal, 2023.143545.) inserted flame retardant nanofibers between the layers of composite materials to make the composite materials flame retardant, with higher strength and toughness. Naidu et al. (International Journal of Biological Macromolecules, 2021.03.035) improved the mechanical properties and barrier properties of xylan-alginate membranes by incorporating CNFs into the xylan-alginate matrix.

[0005] Seaweed polysaccharides are mainly derived from brown algae and are composed of alternating β-d-mannuronic acid and α-l-guluronic acid. The properties of seaweed polysaccharides depend on the monomer sequence, which makes them a material with many uses. They can be used to make films by interacting with divalent and trivalent metal cations to produce crosslinks. Due to its easy availability of raw materials, low cost, biocompatibility and biodegradability.

[0006] Vermiculite is a clay mineral material composed of aluminum and magnesium silicates, with a two-dimensional structural arrangement and a layered morphology. Due to its abundant reserves and low price, it has been used in various fields such as pottery, ceramics, building materials, paper coatings, cosmetics, medicine, decoration and artwork since the birth of mankind. As one of the environmentally friendly natural silicate minerals, vermiculite has a unique layered structure and stable physical and chemical properties. At the same time, it also has a high porosity and low interlayer binding energy, and is easy to peel off to form two-dimensional vermiculite nanosheets to construct new composite functional materials. There are two main methods for preparing two-dimensional vermiculite nanosheets: peeling method and chemical vapor deposition method. The peeling method is a common method for preparing two-dimensional vermiculite nanosheets, but there are problems such as low film strength, uncontrollable sample thickness and low efficiency caused by ordinary mixing. In contrast, the chemical vapor deposition method has a wider range of applications, but it is expensive and requires harsh preparation conditions, which is not conducive to large-scale preparation. Although my country has achieved phased results in the research and development of vermiculite products, the essential properties of vermiculite have not been fully developed, and its added value is low. There is a large amount of waste of raw materials, and large-scale and efficient peeling cannot be achieved, which restricts its further application. Summary of the invention:

[0007] The purpose of the present invention is to solve the shortcomings and deficiencies of the prior art, and propose a high-toughness weather-resistant barrier film and an in-situ cross-linking preparation method thereof, using vermiculite and seaweed polysaccharide as raw materials, the carboxyl groups on the surface of seaweed polysaccharide interact with the hydroxyl groups on the surface of vermiculite, so that the seaweed polysaccharide adheres to the surface of the vermiculite and inserts into the interlayer of the bulk vermiculite, in addition, the seaweed polysaccharide and the vermiculite interlayer ions are cross-linked, further increasing the interlayer spacing of the vermiculite to facilitate the peeling of the vermiculite nanosheets, and preparing a composite film with good flame retardancy, high mechanical strength, environmental friendliness and good freshness preservation performance. .

[0008] In order to achieve the above object, the present invention provides an in-situ cross-linking preparation method of a high-toughness weather-resistant barrier film, the specific steps of which are:

[0009] (1) dispersing two-dimensional layered mineral nanosheets in water and stirring at room temperature to obtain a nanosheet suspension;

[0010] Wherein, the two-dimensional layered mineral is at least one of vermiculite, kaolinite, montmorillonite, illite or chlorite;

[0011] The stirring speed at room temperature is 400-1000r / min;

[0012] The concentration of the nanosheet suspension is 0.1wt% to 0.5wt%;

[0013] (2) slowly adding biomacromolecule polysaccharide to the nanosheet suspension, stirring until the biomacromolecule polysaccharide is completely dissolved, and then adding a plasticizer to obtain a casting solution after the two are evenly blended;

[0014] Wherein, the biomacromolecule polysaccharide is at least one of seaweed polysaccharide, chitosan, carrageenan, sodium carboxymethyl cellulose, chitin and gelatin;

[0015] The amount of the biomacromolecule polysaccharide is 1wt% to 10wt% of the two-dimensional layered mineral nanosheet suspension;

[0016] The stirring speed at room temperature is 400-1000r / min, and the stirring time is 2-24h;

[0017] The plasticizer is glycerol, and its usage is 1v / v% to 5v / v% of the two-dimensional layered mineral nanosheet suspension;

[0018] (3) pouring the casting solution into a mold and drying it to obtain a film precursor;

[0019] Wherein, the drying temperature is 10-80°C;

[0020] The mold is a culture dish with a diameter of 9 cm;

[0021] (4) immersing the film precursor in a metal ion salt solution coagulation bath for crosslinking, and washing and drying after the crosslinking is completed to obtain a high-strength and tough weather-resistant barrier film;

[0022] Wherein, the metal ion salt solution contains Ca 2+ , Cu 2+ or Mg 2+ At least one of;

[0023] The concentration of metal ions in the metal ion solution is 1 mol / L to 5 mol / L;

[0024] The soaking and cross-linking time is 0.5h to 3h.

[0025] The present invention also provides a high-toughness weather-resistant barrier film prepared by the method.

[0026] The high-toughness weather-resistant barrier film has high mechanical strength and also has flame retardant and gas barrier properties.

[0027] The present invention also provides application of the high-toughness weather-resistant barrier film in flame-retardant materials.

[0028] The present invention also provides the use of the high-toughness weather-resistant barrier film in food or fruit preservation. The high-toughness multifunctional composite film can be used as a preservative film to extend the preservation time of food or fruit.

[0029] The preparation principle of this application is:

[0030] There are a large number of hydroxyl groups on the surface of the two-dimensional nanosheets, which interact with the carboxyl groups on the surface of seaweed polysaccharides to form hydrogen bonds, and the interfacial bonding between the two is enhanced. The seaweed polysaccharides adhere to the surface of vermiculite and insert into the interlayer of the bulk vermiculite. There are certain cations (e.g., Ca 2+ Mg 2+ or Fe 3+ etc.), cross-linking with seaweed polysaccharide, further increasing the interlayer spacing of vermiculite and weakening the interlayer interaction force, and achieving the purpose of peeling vermiculite under the action of external shear force. The addition of an appropriate amount of vermiculite nanosheets creates a certain physical barrier that makes the permeation and diffusion paths of the gas more tortuous, so the film has excellent gas barrier properties, which is convenient for maintaining a stable gas environment. At the same time, the interaction between seaweed polysaccharide and vermiculite forms hydrogen bonds, the interlayer ionic cross-linking between seaweed polysaccharide and vermiculite forms an "egg box" structure, and glycerol acts as a plasticizer, which synergistically makes the film have higher toughness. In addition, seaweed polysaccharide itself has intrinsic flame retardant properties, and vermiculite has good thermal stability and can produce flame retardant gas when burning, which significantly improves the flame retardancy of the composite film. Seaweed polysaccharide and vermiculite nanosheets are mixed to form a uniform suspension, which has a certain light transmittance; and the uniform aggregation of two-dimensional vermiculite nanosheets forms a homogeneous film, which shows a good shielding effect in the ultraviolet region, and can slow down the aging of food caused by ultraviolet rays. The film can be directly prepared by mixing in one step, and the process is simple and easy to scale up.

[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0032] 1. The preparation method of the present invention firstly utilizes the intercalation effect of seaweed polysaccharide to expand the interlayer spacing of vermiculite nanosheets, and at the same time, the seaweed polysaccharide and the vermiculite interlayer cations are cross-linked to further expand the interlayer spacing of the vermiculite and weaken the interlayer interaction, thereby achieving the purpose of peeling the vermiculite nanosheets.

[0033] 2. The interlayer structure of the two-dimensional vermiculite nanosheets in the present invention creates a physical barrier that makes the gas permeation and diffusion path more tortuous, significantly improving the gas barrier property of the film, thereby facilitating the formation of a stable gas environment and facilitating the storage and preservation of food.

[0034] 3. The composite film of the present invention has good transparency in the visible light region due to the uniform distribution of an appropriate amount of vermiculite in sodium alginate; the uniform aggregation of two-dimensional vermiculite nanosheets forms a homogeneous film, which shows a good shielding effect in the ultraviolet region, preventing food from deteriorating due to ultraviolet rays, thereby extending the storage time of food.

[0035] 4. In the preparation method of the present invention, the addition of plasticizer significantly improves the flexibility and stretchability of the film.

[0036] 5. The preparation method of the present invention is simple, economical and easy to scale up.

[0037] In summary, the composite film prepared by the present invention has good mechanical properties, and has flame retardancy and gas barrier properties, and can be used for flame retardancy as well as food storage and preservation; the addition of vermiculite increases the ultraviolet shielding effect of the composite film, prevents food from being affected by ultraviolet rays and deteriorating, and prolongs the storage time of food; the preparation method is simple, low in cost, universal, and has good repeatability, is suitable for large-scale promotion, has broad market prospects, and is environmentally friendly. Description of the drawings:

[0038] Figure 1 It is a schematic diagram of the process of preparing the composite membrane of the present invention.

[0039] Figure 2 The composite membrane and CA membrane prepared in Examples 1-5 of the present invention are actual pictures.

[0040] Figure 3 This is a SEM image of the VMT-CA composite membrane of Example 1 of the present invention, wherein A is the CA membrane and B is the VMT-CA composite membrane.

[0041] Figure 4 The XRD patterns of the VMT-CA composite film, calcium alginate film and vermiculite powder of Example 1 of the present invention are shown in FIG.

[0042] Figure 5 This is the infrared spectrum of the VMT-CA composite film, calcium alginate film and vermiculite powder prepared in Example 1 of the present invention.

[0043] Figure 6 It is a schematic diagram of the results of the gas barrier property experiment of the VMT-CA composite film involved in the present invention.

[0044] Figure 7 This is a stress comparison diagram of the VMT-CA composite film and the calcium alginate film involved in the present invention.

[0045] Figure 8 It is a stress comparison diagram of the VMT-CA composite fiber and the calcium alginate fiber involved in the present invention.

[0046] Fig. 9 This is a flame retardant performance test diagram of the VMT-CA composite film involved in the present invention, wherein A is a combustion actual object diagram and B is a limiting oxygen index diagram.

[0047] Fig.10 This is a limiting oxygen index diagram of the VMT-CA composite fiber and calcium alginate fiber involved in the present invention.

[0048] Fig.11 The present invention relates to ultraviolet spectra of the VMT-CA composite film, calcium alginate film and commercial PE film.

[0049] Fig.12 This is a comparison diagram of the effects of the VMT-CA composite film and the calcium alginate film involved in the present invention on fruit preservation and storage, wherein A is a sunshine rose and B is a strawberry. Specific implementation method:

[0050] The present invention is further described below through specific embodiments in conjunction with the accompanying drawings.

[0051] Embodiment 1:

[0052] This embodiment relates to an in-situ cross-linking preparation method for a high-toughness weather-resistant barrier film, specifically:

[0053] (1) Weigh 0.03 g of vermiculite nanosheets and disperse them in 30 mL of deionized water to prepare a 0.1 wt% nanosheet suspension;

[0054] (2) slowly adding 0.3 g of sodium alginate to the nanosheet suspension and stirring it thoroughly at room temperature to dissolve it; then adding 1 mL of glycerol and stirring it thoroughly to form a casting solution;

[0055] (3) pouring the casting solution into a mold and drying it to obtain a thin film precursor; the drying temperature is 50° C.; the mold is a culture dish with a diameter of 9 cm;

[0056] (4) The film precursor was immersed in a calcium chloride solution with a concentration of 5 mol / L for cross-linking for 45 minutes, and the cross-linked film was washed and dried to obtain a high-strength and tough weather-resistant barrier film, which was recorded as 0.1 wt% VMT-CA composite film.

[0057] The obtained product was characterized as follows:

[0058] The surface morphology of the prepared VMT-CA composite film was observed by scanning electron microscopy (SEM), and the calcium alginate film (CA) prepared according to the above method without adding vermiculite nanosheets was used for comparison. Figure 3 As shown. Figure 3 It can be seen that the surface of the calcium alginate film prepared without adding two-dimensional vermiculite powder is smooth, while the surface of the VMT-CA composite film is uneven, and a large amount of vermiculite powder can be seen dispersed thereon.

[0059] X-ray powder diffraction (XRD) was used to characterize the phase structure and crystal form of the synthesized VMT-CA composite film. Figure 4 The diffraction peak of vermiculite (VMT) powder appears at 8.759°, while the VMT-CA composite film has a strong diffraction peak at this position and also a diffraction peak at 6.02°. This indicates that the intercalation of seaweed polysaccharides into vermiculite increases the interlayer spacing.

[0060] The chemical properties of VMT-CA membrane, CA membrane and vermiculite powder were characterized by Fourier transform infrared spectroscopy (FTIR). Figure 5 As shown. Vermiculite powder at 990cm -1 The strong peak at about 708 cm-1 can be attributed to the asymmetric stretching vibration of Si-O-Si. -1 The peak at 1590 cm-1 indicates the presence of Al-O bonds on the membrane surface. -1 The characteristic peaks at are C=O and 1417 cm -1 The characteristic peak at is COO - The VMT-CA composite membrane has a -1 and 616cm -1 There is a characteristic peak at - and Al-O stretching vibrations, indicating that seaweed polysaccharides have been successfully grafted into vermiculite.

[0061] Embodiment 2:

[0062] This embodiment relates to an in-situ cross-linking preparation method for a high-toughness weather-resistant barrier film, specifically:

[0063] (1) Weigh 0.06 g of vermiculite nanosheets and disperse them in 30 mL of deionized water to prepare a 0.2 wt % nanosheet suspension;

[0064] (2) Slowly add 0.3 g of sodium alginate to the nanosheet suspension and stir thoroughly at room temperature. Then add 1 mL of glycerol and stir thoroughly to form a casting solution;

[0065] (3) pouring the casting solution into a mold and drying it to obtain a film precursor; the drying temperature is 40° C.; the mold is a culture dish with a diameter of 9 cm;

[0066] (4) The film precursor was immersed in a calcium chloride solution with a concentration of 5 mol / L for cross-linking for 45 minutes, and the cross-linked film was washed and dried to obtain a high-strength and tough weather-resistant barrier film, which was recorded as 0.2 wt% VMT-CA composite film.

[0067] Embodiment 3:

[0068] This embodiment relates to an in-situ cross-linking preparation method for a high-toughness weather-resistant barrier film, specifically:

[0069] (1) Weigh 0.09 g of vermiculite nanosheets and disperse them in 30 mL of deionized water to prepare a 0.3 wt % nanosheet suspension;

[0070] (2) Slowly add 0.3 g of sodium alginate to the nanosheet suspension and stir thoroughly at room temperature. Then add 1 mL of glycerol and stir thoroughly to form a casting solution;

[0071] (3) pouring the casting solution into a mold and drying it to obtain a thin film precursor; the drying temperature is 10° C.; the mold is a culture dish with a diameter of 9 cm;

[0072] (4) The film precursor was immersed in a calcium chloride solution with a concentration of 5 mol / L for cross-linking for 45 minutes, and the cross-linked film was washed and dried to obtain a high-strength and tough weather-resistant barrier film, which was recorded as a 0.3 wt% VMT-CA composite film.

[0073] Embodiment 4:

[0074] This embodiment relates to an in-situ cross-linking preparation method for a high-toughness weather-resistant barrier film, specifically:

[0075] (1) Weigh 0.12 g of vermiculite nanosheets and disperse them in 30 mL of deionized water to prepare a 0.4 wt % nanosheet suspension;

[0076] (2) Slowly add 0.3 g of sodium alginate to the nanosheet suspension and stir thoroughly at room temperature. Then add 1 mL of glycerol and stir thoroughly to form a casting solution;

[0077] (3) pouring the casting solution into a mold and drying it to obtain a thin film precursor; the drying temperature is 70° C.; the mold is a culture dish with a diameter of 9 cm;

[0078] (4) The film precursor was immersed in a calcium chloride solution with a concentration of 5 mol / L for cross-linking for 45 minutes, and the cross-linked film was washed and dried to obtain a high-strength and tough weather-resistant barrier film, which was recorded as 0.4 wt% VMT-CA composite film.

[0079] Embodiment 5:

[0080] This embodiment relates to an in-situ cross-linking preparation method for a high-toughness weather-resistant barrier film, specifically:

[0081] (1) Weigh 0.15 g of vermiculite nanosheets and disperse them in 30 mL of deionized water to prepare a 0.5 wt % nanosheet suspension;

[0082] (2) Slowly add 0.3 g of sodium alginate to the nanosheet suspension and stir thoroughly at room temperature. Then add 1 mL of glycerol and stir thoroughly to form a casting solution;

[0083] (3) pouring the casting solution into a mold and drying it to obtain a thin film precursor; the drying temperature is 80° C.; the mold is a culture dish with a diameter of 9 cm;

[0084] (4) The film precursor was immersed in a calcium chloride solution with a concentration of 5 mol / L for cross-linking for 45 minutes, and the cross-linked film was washed and dried to obtain a high-strength and tough weather-resistant barrier film, which was recorded as 0.5 wt% VMT-CA composite film.

[0085] Embodiment 6:

[0086] This embodiment relates to an in-situ cross-linking preparation method for a high-toughness weather-resistant barrier film, specifically:

[0087] (1) Weighing 0.03 g of kaolin nanosheets and dispersing them in deionized water to prepare a 0.1 wt % nanosheet suspension;

[0088] (2) slowly adding 0.3 g of sodium alginate to the nanosheet suspension and stirring thoroughly at room temperature; then adding 0.5 mL of glycerol and stirring thoroughly to form a casting solution;

[0089] (3) pouring the casting solution into a mold and drying it to obtain a film precursor; the drying temperature is 80° C.;

[0090] (4) The film precursor is immersed in a calcium chloride solution with a concentration of 5 mol / L for cross-linking for 45 minutes, and the cross-linked film is washed and dried to obtain a high-strength and weather-resistant barrier film.

[0091] Embodiment 7:

[0092] This embodiment relates to an in-situ cross-linking preparation method for a high-toughness weather-resistant barrier film, specifically:

[0093] (1) Weighing 0.15 g of montmorillonite nanosheets and dispersing them in deionized water to prepare a 0.5 wt % nanosheet suspension;

[0094] (2) slowly adding 1 g of sodium alginate to the nanosheet suspension, stirring thoroughly at room temperature, and then adding 2 mL of glycerol, stirring thoroughly to form a casting solution;

[0095] (3) pouring the casting solution into a mold and drying it to obtain a film precursor; the drying temperature is 20° C.;

[0096] (4) The film precursor is immersed in a calcium chloride solution with a concentration of 5 mol / L for cross-linking for 45 minutes, and the cross-linked film is washed and dried to obtain a high-strength and weather-resistant barrier film.

[0097] Embodiment 8:

[0098] This example relates to the performance test of the VMT-CA composite membrane.

[0099] 1. Gas barrier properties,

[0100] The mouths of bottles containing 10 g of deionized water, 10 g of ethanol and 10 g of acetone were covered and sealed with 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt% and 0.5 wt% VMT-CA composite films, calcium alginate (CA) films, weighing paper and bottle caps prepared by the preparation methods of Examples 1-5, respectively. An open bottle containing 10 g of deionized water, 10 g of ethanol and 10 g of acetone was used as a comparison. The bottles were weighed at a fixed time every day. The water vapor weight loss rate was calculated after 8 days. The results are as follows Figure 6 shown.

[0101] from Figure 6 It can be seen that the bottles sealed with the five VMT-CA composite films show a smaller water vapor weight loss rate than the open bottles. For ethanol and acetone, the vapor permeability of the 0.2wt% VMT-CA composite film and the bottle sealed with the bottle cap is almost the same. The results show that the composite film has good barrier properties to organic matter.

[0102] 2. Stress test

[0103] The VMT-CA composite films prepared in Examples 1-5 were subjected to stress tests using a flexible electronic in-situ testing platform, and the VMT-CA composite films without glycerol and the CA films with / without glycerol were compared. The results are shown in FIG. Figure 7 As shown. Figure 7 It can be seen that the addition of glycerol helps the composite film to obtain higher mechanical strength, and compared with the calcium alginate film, the tensile strength of the VMT-CA composite film is improved. With the increase of vermiculite content, the tensile strength of the VMT-CA composite film gradually increases. The tensile stress comparison results confirm that the addition of vermiculite nanosheets and glycerol helps to improve the mechanical properties of the VMT-CA composite film. The addition of vermiculite nanosheets can be used as an adhesive to enhance the interfacial bonding strength of the composite film by forming hydrogen bonds with seaweed polysaccharides; at the same time, the seaweed polysaccharides and vermiculite interlayer ions form cross-linking chemical bonds to further improve the tensile properties.

[0104] The single fiber tensile test of VMT-CA composite fiber and calcium alginate fiber was carried out using a fiber strength, elongation and fineness tester. The results are as follows: Figure 8 As shown. Figure 8 It can be seen that the addition of VMT improves the tensile strength of the fiber; the strength of 0.2wt% VMT-CA composite fiber is 46.0% higher than that of pure calcium alginate fiber.

[0105] The preparation method of the VMT-CA composite fiber is as follows: 0.5g of vermiculite nanosheets are weighed and dispersed in 500mL of deionized water to prepare a 0.1wt% nanosheet suspension. Then 20g of sodium alginate is slowly added thereto and fully stirred at room temperature to prepare a spinning solution; 5% by mass of calcium chloride is prepared as a coagulation bath aqueous solution. The spinning solution is allowed to stand for 12h to fully degas and then extruded into a coagulation bath aqueous solution for cross-linking and forming, and the VMT-CA composite fiber is obtained after drawing and washing.

[0106] 3. Flame retardant test

[0107] The flame retardancy of the VMT-CA composite film and the calcium alginate film of Examples 1-5 was tested using a limiting oxygen index tester. The combustion pictures and test results of the VMT-CA composite film and the calcium alginate film are as follows: Fig. 9 As shown. The higher the LOI value, the better the flame retardant performance of the sample. Fig. 9 It can be seen that the limiting oxygen index of 0.1wt% VMT-CA is 35.0%, which has initial flame retardant properties, and the addition of vermiculite further improves the flame retardant properties of the composite film, up to 41.9%. This is mainly attributed to the good carbon-forming ability of seaweed polysaccharides during the combustion process. The coke produced forms a protective layer, which reduces the oxygen supply and thus inhibits the combustion reaction and extinguishes the flame; at the same time, vermiculite has inherent good thermal stability and contains refractory compounds such as SiO2, Al2O3 and MgO. During the combustion process, it can release flame retardant gases such as H2O, CO2, NO and SO2. The embedding of seaweed polysaccharides into the interlayer of vermiculite can reduce the rapid transfer of heat, further improving the flame retardancy of the VMT-CA composite film. This can also be witnessed from the flame retardant physical picture. The CA film has been completely burned in 96s; while the VMT-CA film has a smoldering phenomenon, the smoldering time is long and the combustion speed is slow, and it cannot be completely burned out, and basically stops burning after 80 seconds.

[0108] At the same time, the flame retardancy of VMT-CA composite fiber and calcium alginate fiber was tested. Fig.10 As shown. Fig.10 It can be seen that the flame retardant properties of calcium alginate fiber are better with the increase of vermiculite content, and the flame retardant properties of 0.5wt% VMT-CA composite fiber are 28.1% higher than those of pure calcium alginate fiber.

[0109] 3. Light blocking performance test

[0110] The light barrier properties and opacity of the VMT-CA composite films, CA films and commercial PE films of Examples 1-5 were comprehensively analyzed using a UV-visible spectrophotometer. The results are as follows: Fig.11 As shown. Fig.11It can be seen that the transmittance of commercial PE film in the ultraviolet region (200-400nm) is above 60%, which has a poor ultraviolet shielding effect. In contrast, the transparency of CA film in the visible light region is comparable to that of commercial PE film, and its shielding effect in the ultraviolet region is much better than that of commercial PE film. And with the increase of vermiculite content, the ultraviolet shielding effect of VMT-CA composite film gradually increases. The 0.2wt% VMT-CA and 0.3wt% VMT-CA composite films can ensure both good transparency and good ultraviolet shielding effect.

[0111] 4. Freshness preservation effect test

[0112] In order to test the actual effect of VMT-CA composite film in packaging and preservation, fruits (sunrise roses and strawberries) of uniform size, no physical damage on the surface and similar maturity were selected and placed in containers. Then, the containers were sealed with pure calcium alginate film, VMT-CA composite film and commercial PE respectively. Uncovered containers were selected as the control group and stored under constant temperature and humidity (25℃, RH=45%). The actual picture of the fruit changing over time, such as Fig.12 As shown. Fig.12 A shows that the Sunshine Rose sealed with pure calcium alginate film started to deteriorate slightly on the 5th day, the control group on the 3rd day, and the commercial PE film on the 7th day. Then, on the 15th day, a large number of black molds appeared on the stems of the Sunshine Rose sealed with the commercial PE film. In contrast, the Sunshine Rose sealed with the VMT-CA composite film showed no rot on the surface on the 15th day, but only shrunk slightly and was still edible, with a good preservation effect. Fig.12 B It can be seen that the fresh-keeping storage time of strawberries sealed with VMT-CA composite film can be extended to 8 days.

Claims

1. An in-situ cross-linking preparation method for a high-toughness weather-resistant barrier film, characterized in that: The following steps are involved: (1) dispersing two-dimensional layered mineral nanosheets in water and stirring at room temperature to obtain a nanosheet suspension; the two-dimensional layered mineral comprises at least one of vermiculite, kaolinite, montmorillonite, illite or chlorite; (2) slowly adding a biomacromolecular polysaccharide to the nanosheet suspension, stirring until the biomacromolecular polysaccharide is completely dissolved, and then adding a plasticizer to obtain a casting solution after the two are evenly blended; the biomacromolecular polysaccharide is at least one of seaweed polysaccharide, chitosan, carrageenan, sodium carboxymethyl cellulose, chitin and gelatin; (3) pouring the casting solution into a mold and drying it to obtain a film precursor; (4) Immersing the film precursor in a metal ion salt solution coagulation bath for crosslinking, washing and drying after the crosslinking is completed, and obtaining a high-strength and tough multifunctional composite film.

2. The in-situ crosslinking preparation method of the high-toughness weather-resistant barrier film according to claim 1, characterized in that: In the step (1), the concentration of the nanosheet suspension is 0.1 wt% to 0.5 wt%.

3. The in-situ cross-linking preparation method of the high-toughness weather-resistant barrier film according to claim 1, characterized in that: In the step (1), the stirring speed is 400-1000 r / min at room temperature.

4. The in-situ crosslinking preparation method of the high-toughness weather-resistant barrier film according to claim 1, characterized in that: In the step (2), the amount of biomacromolecule polysaccharide used is 1 wt% to 10 wt% of the nanosheet suspension.

5. The in-situ cross-linking preparation method of the high-toughness weather-resistant barrier film according to claim 1, characterized in that: In the step (2), the plasticizer is glycerol, and its usage is 1wt% to 5wt% of the nanosheet suspension.

6. The in-situ crosslinking preparation method of the high-toughness weather-resistant barrier film according to claim 1, characterized in that: In the step (3), the drying temperature is 10 to 80°C.

7. The in-situ cross-linking preparation method of the high-toughness weather-resistant barrier film according to claim 1, characterized in that: In the step (4), the metal ion salt solution contains Ca 2+ , Cu 2+ or Zn 2+ At least one of the above, the concentration of metal ions in the metal ion solution is 1 mol / L to 5 mol / L; and the immersion cross-linking time is 0.5h to 3h.

8. The high-toughness weather-resistant barrier film prepared by the preparation method according to any one of claims 1 to 7, characterized in that: It has good mechanical properties and is flame retardant and gas barrier.

9. Use of the high-toughness weather-resistant barrier film according to claim 8 in flame retardant materials.

10. Use of the high-toughness weather-resistant barrier film according to claim 8 in food or fruit preservation, characterized in that: The high-strength and tough multifunctional composite film can be used as a cling film to extend the shelf life of food or fruit.

Citation Information

Cited By

  • Incense-burning oxygen-consuming carbon dioxide-supplementing food preservation bag for household refrigerator

    CN224455047U